3D CAD modeling of deep drawing tools based on a new graphical language. Issue 5 (3rd September 2018) - Koch, Sergej; Behrens, Bernd-Arno; Hübner, Sven; Scheffler, Robert; Wrobel, Gregor; Pleßow, Matthias; Bauer, David
ABSTRACT: Increasing diversity of types and decreasing batch sizes along with a growing complexity of products manufactured by forming technology result in new challenges for developers and designers. The construction of a full parametric model of a deep drawing tool in a 3D CAD system is usually considered time-consuming and associated with high cost, and thus discourages many designers. In order to render this type of modeling easier and faultless, a new method for the model-driven design of deep drawing tools is developed. For this purpose the analysis of fully parametric 3D CAD models of deep drawing tools is necessary. This analyzing contributes to the newly developed graphical domain-specific language, which makes the modeling of deep drawing tools more flexible and time-efficient. GRAPHICAL ABSTRACT: